Incidence of contrast-induced acute kidney injury in a large cohort of all-comers undergoing percutaneous coronary intervention: Comparison of five contrast media. (15th December 2018) - Azzalini, Lorenzo; Vilca, Luz María; Lombardo, Francesca; Poletti, Enrico; Laricchia, Alessandra; Beneduce, Alessandro; Maccagni, Davide; Demir, Ozan M.; Slavich, Massimo; Giannini, Francesco; Carlino, Mauro; Margonato, Alberto; et al.
Abstract: Background: There is controversy as to whether iso-osmolar contrast media (IOCM) are associated with lower risk of contrast-induced acute kidney injury (CI-AKI), compared with low-osmolar contrast media (LOCM). We aimed to evaluate if a differential risk of CI-AKI exists after percutaneous coronary intervention (PCI) according to different contrast media (CM) types. Methods: We performed a single-center retrospective study in a cohort of all-comers undergoing PCI between January 2012 and December 2016. CI-AKI was defined as an increase in serum creatinine ≥0.3 mg/dl or ≥50% within 72 h from PCI. IOCM were represented by iodixanol, whereas four different LOCM were utilized (ioversol, iopromide, iomeprol, iobitridol). Multiple-treatment inverse probability of treatment weighting (IPTW)-adjusted logistic regression analysis was performed to identify whether CM type was an independent predictor of CI-AKI. Results: We included 2648 subjects (ioversol, n = 272; iopromide, n = 818; iomeprol, n = 611; iobitridol, n = 460; iodixanol, n = 487). CI-AKI occurred in 300 patients (11.7%) overall, with no differences across CM groups (ioversol 13.0%, iopromide 11.5%, iomeprol 10.2%, iobitridol 13.9%, iodixanol 11.3%; p = 0.42). CI-AKI requiring dialysis was observed in 8 patients (0.3%) overall (p = 0.50). On IPTW-adjusted analysis, none of the LOCM was associated with a significantly different risk of CI-AKI compared with iodixanol: ioversol OR 0.986 (95% confidence interval [CI] 0.611–1.591), iopromide OR 0.870 (95% CI 0.606–1.250), iomeprol OR 0.904 (95% CI 0.619–1.319), iobitridol OR 1.258 (95% CI 0.850–1.861). Conclusions: In a large cohort of all-comers undergoing PCI, there were no differences in the adjusted risk of CI-AKI across 4 LOCM, compared with iodixanol. Highlights: Contrast-induced acute kidney injury has a high incidence (11.7%) in all-comers undergoing (mostly complex) PCI The unadjusted rates of contrast-induced acute kidney injury are similar across five different types of contrast media Contrast-induced acute kidney injury requiring dialysis was observed in only 0.3% of patients The adjusted risk of contrast-induced acute kidney injury was similar across low-osmolar and iso-osmolar contrast media